Computerized land registration systems - Molen, Paul van der (Technical Centre for Agricultural and Rural Cooperation, 2005)
Paul van der Molen explains that unless adequate policies and institutions are in place, computerization will not necessarily reduce land tenure insecurity or improve the management of land resources